Economic Students’ Perceptions Towards Learning Management System (LMS) - Irene Brainnita Oktarin; Kristina Estisari; Tyas Desita Wengrum; Adhi Nurhantanto (Journal of Arts and Education, 2023)
The objectives of this study is to determine the perceptions of Economic students towards online learning by using Learning Management System (LMS). This study used qualitative descriptive method. The data was obtained by distributing questionnaires to 30 students in Management study program after completing 8 meetings learning process. The result  of this study shows that (1) the use of Learning Management System (LMS) provides new experiences in online learning activities; (2) students can operate some features of Learning Management System (LMS) easily; (3) students use Learning Management System (LMS) because the learning process expects them to use it; (4) Learning Management System (LMS) is one of platform that can support online learning activities; (5) the use of Learning Management System (LMS) is because students classmates agree to use it; and (6) students can use Learning Management System (LMS) easily in carrying out online learning activities. Keywords : students, perceptions, Learning Management System (LMS)